A numerical technique for solving nonlinear singularly perturbed delay differential equations - Kanth, A.S.V. Ravi; P. Murali, Mohan Kumar (Mathematical modelling and analysis, 2018)
This paper presents a numerical technique for solving nonlinear singularly perturbed delay differential equations. Quasilinearization technique is applied to convert the nonlinear singularly perturbed delay differential equation into a sequence of linear singularly perturbed delay differential equations. An exponentially fitted spline method is presented for solving sequence of linear singularly perturbed delay differential equations. Error estimates of the method is discussed. Numerical examples are solved to show the applicability and efficiency of the proposed scheme.